Answer:
y = x² − x + 3
Step-by-step explanation:
Quadratic equation is:
y = ax² + bx + c
Pick three points and plug in. I'll choose (-2, 9), (-1, 5), and (0, 3).
9 = a(-2)² + b(-2) + c
5 = a(-1)² + b(-1) + c
3 = a(0)² + b(0) + c
9 = 4a − 2b + c
5 = a − b + c
3 = c
We know c = 3, so substitute into the first two equations:
9 = 4a − 2b + 3
5 = a − b + 3
0 = 4a − 2b − 6
0 = a − b − 2
Solve by elimination or substitution.
b = a − 2
0 = 4a − 2(a − 2) − 6
0 = 4a − 2a + 4 − 6
0 = 2a − 2
a = 1
b = -1
Therefore:
y = x² − x + 3